Drug approval processes in Australian Paediatric Hospitals. Issue 9 (28th June 2010) - Sinha, Y K; Craig, J C; Barclay, P; Taitz, J; South, M; Coulthard, K; Pearson, C; Erickson, S; Brien, J E
Abstract : Objective: To describe and evaluate the decision-making processes for drug approval in Australian paediatric hospitals. Design: Multicentre descriptive study involving face-to-face interviews of drug and therapeutics committee chairs and secretaries, review of committee documents and drug submissions for all Australian paediatric hospital drug and therapeutics committees over a 1-year period. Setting: All eight paediatric hospitals in Australia. Participants: Eight committee chairs and seven secretaries or delegates. Main outcome measures: Total drug expenditure, number of formulary submissions, individual-patient use approvals and approval rates for each hospital from 1 July 2006 to 30 June 2007, stratified by therapeutic class. Qualitative description of the approval processes. Results: Total drug expenditure varied from A1.7 million (US1.5 million) to A11.1million (US9.8 million) per hospital. The number of formulary submissions also varied, from 7 to 21, but approval rate was high (76%–100%) and not significantly different among hospitals (p=0.17). Several committees approved identical submissions for five drugs. The number of individual-patient use applications varied considerably, ranging from 10 to 456 per hospital. Where estimable, individual-patient use approval was 76%–100% and variable (p=0.03). Quality of evidence relating to safety and efficacy of drugs being considered was regarded as the most important factors influencing decision making, with the cost less important. Most committees had poor infrastructural support for approval processes. No committee formally included a pharmaco-economic evaluation. Conclusions: Most drug submissions in tertiary paediatric hospitals are approved; however, workload, drug expenditure and individual-patient use schemes vary considerably. Duplication of effort occurs, and few committees are resourced sufficiently given their terms of reference.